1983
DOI: 10.3168/jds.s0022-0302(83)81776-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing upon Concentration and Distribution of Natural and lodophor-Derived Iodine in Milk

Abstract: Cream removal, pasteurization, and spray-drying of milk did not affect concentration of either natural or iodophor-derived iodine, as measured by both chemical and electrode methods, although electrode results were significantly higher. The use of iodine-131 labeled iodophor showed that only .02% of iodine was lost from milk on boiling and that 3.4% of iodophor-iodine became associated with milk casein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…One report suggests that heating or boiling during pasteurization reduce the iodine content of the milk by 20%. As well, it has been reported that spray and roller drying of milk reduces iodine concentration by 40% [17]. Pedriali et al [18] reported that heat processing during pasteurization can be able to decrease 33% of milk iodine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…One report suggests that heating or boiling during pasteurization reduce the iodine content of the milk by 20%. As well, it has been reported that spray and roller drying of milk reduces iodine concentration by 40% [17]. Pedriali et al [18] reported that heat processing during pasteurization can be able to decrease 33% of milk iodine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications indicate that milk pasteurization results in an approximate reduction in the iodine concentration of at least 27% (Wheeler et al, 1983;Aumont et al, 1987;Pedriali et al, 1997;Norouzian, 2011). Food processing should be considered before estimating consumer exposure.…”
Section: Assessment Of Consumer Safetymentioning
confidence: 99%
“…Most (80-90%) of the iodine in cow's milk is in the inorganic form, mainly as iodide, and is in the water-soluble fraction (Miller et a/., 1975;Wheeler et a/., 1983), and 5-13% is bound to proteins through either covalent bonds or loose physical associations, with less than 0.1% to fat (Murthy and Campbell, 1960;Miller eta/., 1975). Iodide is rapidly, and almost completely, absorbed, but organically bound iodine is less well absorbed (NRC, 1989a).…”
Section: Iodinementioning
confidence: 99%